Ecological and evolutionary processes that shape the long-distance migrations of birds (2017)
Migration results in predictable, seasonal movements of millions of animals across the globe. Not only is migration an impressive natural phenomenon, but it is involved in ecological and evolutionary processes ranging from determining individual fitness and population dynamics, to influencing speciation and ecosystem functioning. All events in the annual cycle of migrants are intricately linked. One event which has been shown to significantly affect population dynamics, is migration. The strategies birds use to optimize their movements are known as migratory strategies. Depending on body condition, age, sex, date, weather, distance to destination and evolutionary constraints, birds may choose to fly directly or make few stops along the way. How birds carry out this optimization of their migratory strategies is not well understood and likely varies in different species. By studying bird migration with the use behavioral observations, capture-recapture, intercontinental telemetry, stable isotopes and genetics, I generated information about the evolution of migratory strategies, how different biotic and abiotic factors affect them, how flexible these strategies appear in the face of climatic or habitat changes and the implications this may have on migratory species conservation. My thesis is divided into four chapters. Chapter 1 proposes a method for the assessment of seasonal changes in animal diets, and an evaluation of the importance of diet during migration. Chapter 2 integrates behavioral data with remote tracking to understand how birds behave during stopover and to quantify the effect of a stopover on the pace of migration. Chapter 3 explores how a migratory bird links two of the planet's greatest forests, the Amazon and the Boreal, via the world's most irreplaceable natural region and center of endemism, the Sierra Nevada de Santa Marta. Finally, Chapter 4 evaluates the temporal dynamics of climatic niche evolution and its relation to migratory behavior